Parental Monitoring Intervention Measures for Distance Learning Modalities (International Journal of Scientific Research and Management (IJSRM), 2023)
Given the escalation of the COVID-19 pandemic and efforts to contain its spread, a large number of educational institutions around the world have completely shut down face-to-face teaching and learning activities. This lockdown exposed emerging vulnerabilities in the world’s education systems in low- and middle-income countries. This lockdown exposed emerging vulnerabilities in the educational sector in low- and middle-income countries around the world, including Philippines. This demonstrates the importance of adaptable and resilient education systems in the face of an uncertain future. The salient findings of the study are as follows: the assessment of teachers and parents on the parental monitoring intervention measures adopted are as follows: all items rated as Effective as to organize, measure, control, and analyze; and the computed t-values in organize, measure, control and analyze were all lower than the critical value, hence, there is no significant difference on parental monitoring intervention measures for distance learning modalities as assessed by teachers and parents.